75 VASCULAR ENDOTHELIAL GROWTH FACTOR SIGNALING BLOCKADE AMELIORATES DIABETIC ALBUMINURIA IN MICE: EFFECTS ON THE KIDNEY PODOCYTE. (1st March 2007) - Chen, S.; Wang, A.; Pyagay, P.; Kanwar, Y. S.; Ziyadeh, F. N.
Abstract : To investigate how the vascular endothelial growth factor (VEGF) system participates in the pathogenesis of diabetic kidney disease, type 2 diabetic db/db and control db/m mice were treated intraperitoneally with vehicle or 2 mg/kg of a pan-VEGF receptor tyrosine kinase inhibitor, SU5416, twice a week for 8 weeks. Efficacy of SU5416 treatment in the kidney was verified by the inhibition of VEGF receptor 1 phosphorylation. Glomerular VEGF immunostaining, normally increased in diabetes, was unaffected by SU5416. The primary end point of albuminuria increased ≈fourfold in the diabetic db/db mice but was significantly ameliorated (almost completely prevented) by SU5416. Correlates of albuminuria were then investigated. Diabetic thickening of the glomerular basement membrane (GBM) was prevented in the SU5416-treated db/db mice, concurrent with the amelioration of albuminuria, whereas diabetic mesangial matrix expansion remained unchanged by treatment. The density of open slit pores between podocyte foot processes, a marker that tracks well with diabetic albuminuria, was decreased in db/db diabetes but was partly increased toward normal by SU5416. Finally, podocyte-based nephrin protein, which correlates inversely with albuminuria and whose mutation is the genetic basis of Finnish congenital nephrotic syndrome, was decreased in the db/db mice by immunofluorescence but was significantly restored by SU5416. Paradoxically, the same nephrin protein measured by Western blotting was increased in diabetes, pointing toward a possible dysregulation of nephrin trafficking. Diabetic albuminuria is partially a function of VEGF receptor signaling overactivity. VEGF signaling was found to affect a number of podocyte-driven manifestations, such as GBM thickening, slit pore density, and nephrin quantity, all of which are associated with the extent of diabetic albuminuria. By impeding these pathophysiologic processes, VEGF receptor inhibition by SU5416 might become a useful adjunct to antialbuminuria therapy in diabetic nephropathy.